Hubungan Asupan Makanan dan Aktivitas Fisik Serta Body Image dengan Status Gizi Lebih Mahasiswa di Poltekkes Kemenkes Makassar - Hikmawati Ma'sud; Abdullah Tamrin; Mustamin Mustamin; Kiki Natasyah (Direktorat Politeknik Kesehatan Makassar, 2024)
In Indonesia, overnutrition status is still relatively high. Excessive food intake, lack of physical activity, and bad body image are some of the causes. The aim of this research is to find out how food intake, physical activity, and body appearance are related to better nutritional status. A cross-sectional design was used in this study. This research sample took a total of 52 individuals. Use of questionnaires to collect variable data. Remember, twice every twenty-four hours is used to collect food intake data. BMI is calculated by measuring height and weight. The relationship between variables was evaluated with the chi-square test. The results showed that there was a significant correlation between energy intake and nutritional status, with a p-value of 0.024 greater than the α value (0.05). It was shown that there was an insignificant relationship between nutritional status and protein intake, with a p value = 0.118 greater than the α value (0.05), fat and carbohydrates, with a p value = 0.011 greater than the α value (0.05), and physical activity, with a p value = 0.620 greater than the α value (0.05). It is recommended that future researchers conduct further research by including additional factors such as fiber intake and stress factors. Keywords: Physical activity; food consumption; body appearance; higher nutritional levels